EVALUASI PROGRAM PEMBELAJARAN REMEDIAL PADA PEMBELAJARAN EKONOMI DI SMA NEGERI 1 DONRI DONRI - Rosdiana, Rosdiana (PEP Educational Assessment, 2017)
This research aims at describing remedial learning programs at SMAN 1 Donri-Donri based on antecedents, transactions, and output components. This research is the kind of evaluation research which employs coutenance stake model, consists of evaluation of antecendents, transactions, and output. The subjects of this research were Economic teacher who conducted the remedial learning program and the students who followed remedial learning program, headmaster, and vice of headmaster at SMAN 1 Donri-Donri in Soppeng district. Data was collected by employing interview and documentation. Data was analysed qualitatively by conducting data collection, data reduction, data presentation, and conclusion. The result of the research reveals that antecedents component of remedial learning programs on Economic learning at SMAN 1 Donri-Donri is not well planned. Based on the transaction component, the remedial learning programs on Economic learning at SMAN 1 Donri-Donri is conductedwell done. Based on the output component, the remedial learning programs on Economic learning at SMAN 1 Donri-Donri has obtained good result.